Rabindranath Tagore - Humayun Kabir, 1906-1969. (Delhi : Pankaj Publications International, 1987)
Lectures on Rabindranath Tagore, 1861-1941, Indian poet.
Originally published: London : School of Oriental and African Studies, 1962. (Tagore lectures ; 1961)
Keywords: Tagore, Rabindranath, -- 1861-1941 -- Criticism and interpretation